Integrated pest management in jute - Sarkar, S K; Satpathy, S; De, R K (Indian Farming, 2022)
Jute (Tossa jute: Corchorus olitorious and White jute: Corchorus capsularis) is an important natural bast fibre yielding crop with considerable commercial, environmental and socio-economic importance. It has multifarious end users and mostly grown in the tropical and south-east Asian countries particularly in India and Bangladesh. Incidence of different pests in jute is the most limiting factor in productivity improvement. Different pests and diseases of jute witnessed a great transformation in the backdrop of climate change with respect to intensity of incidence, development of new strains and susceptibility of host. Any single method of pests control cannot address the management of jute pests in totality. Therefore, holistic approaches through the Integrated Pest Management (IPM) methods starting from sowing to harvesting should be used to address the management of jute pests with economic viability.